8h-1-h+3h=-3

Simple and best practice solution for 8h-1-h+3h=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8h-1-h+3h=-3 equation:



8h-1-h+3h=-3
We move all terms to the left:
8h-1-h+3h-(-3)=0
We add all the numbers together, and all the variables
10h+2=0
We move all terms containing h to the left, all other terms to the right
10h=-2
h=-2/10
h=-1/5

See similar equations:

| 4(x+5)=8+6(2x-2)= | | -3×-9=-2(2x-3)+5 | | 9(x+7)=2(3x+9) | | 4r-2=2 | | 88-36+10+3x-x-2x=180 | | d.2+9=12 | | -25x=11 | | 2x+9=14x+9 | | 6c=14=-5c+4+9c | | 4x+18=15x+18 | | n/4-11=-5 | | n/5-11=5 | | 8(x+3)=2+8x | | 4m+6=-10 | | -3x-17=-7+3x | | 34=-8v+2(v-4) | | m+31=307m= | | 27x+27-9=-2x-5 | | 53=-6-17y | | 3/4(36x+36)-9=-1/5(10x-25) | | |4r-2|=2 | | 1.08^x=8/5 | | 7(x+5)=4x-3-x | | 7x+12=92−3x | | 1.0p-0.35p=8.50 | | 3(y-7)=4(2y+3) | | 5(5-4)=-5x+20 | | 12=3(x+7)-6x | | 6(2x+1)-12=-2(x+10) | | 20n-40=40 | | 53-17=4u+17 | | 2/3y=-6/7 |

Equations solver categories